Controversies and Opportunities in the Use of Inflammatory Markers for Diagnosis or Risk Prediction in Fatty Liver Disease - Lambrecht, Joeri; Tacke, Frank (Frontiers in Immunology, 2021)
In the Western society, non-alcoholic fatty liver disease (NAFLD), characterized by the excessive accumulation of fat in the liver, represents the most common cause of chronic liver disease. If left untreated, approximately 15-20% of patients with NAFLD will progress to non-alcoholic steatohepatitis (NASH), in which lobular inflammation, hepatocyte ballooning and fibrogenesis further contribute to a distorted liver architecture and function. NASH initiation has significant effects on liver-related mortality, as even the presence of early stage fibrosis increases the chances of adverse patient outcome. Therefore, adequate diagnostic tools for NASH are needed, to ensure that relevant therapeutic actions can be taken as soon as necessary. To date, the diagnostic gold standard remains the invasive liver biopsy, which is associated with several drawbacks such as high financial costs, procedural risks and inter/intra-observer variability in histology analysis. As liver inflammation is a major hallmark of disease progression, inflammation-related circulating markers may represent an interesting source of non-invasive biomarkers for NAFLD/NASH. Examples for such markers include cytokines, chemokines or shed receptors from immune cells, circulating exosomes related to inflammation, and changing proportions of peripheral blood mononuclear cell (PBMC) subtypes. This review aims at documenting and critically discussing the utility of such novel inflammatory markers for NAFLD/NASH-diagnosis, patient stratification and risk prediction.